An Investigation Study Between Two Genders, Public And Private Schools, Through The Achievement Of The Pupils In The Exact Sciences: A Case Study Of Selected Secondary Schools In Conakry, Guinea - Toure, Alhassane; Guoxin, Zuo (European Scientific Journal, ESJ, 2016)
We are in a changing society through which the equality of boys and girls has become a major scourge. In this study, we demonstrated in the first step, a comparative study between the scores of boys and girls in three different subjects (mathematics, physics and chemistry) at secondary level. The second was to conduct a survey through a questionnaire on the satisfaction of parents on the two types of schools (public and private) and their realization in the exact sciences. The investigation put into account the fact that some high schools are selected randomly in the capital Conakry after their preparatory examinations. The first comparative method used is descriptive and explanatory design based on a sample of 1,400 school students terminal (TSM and TSE) in three schools in the capital. From the results obtained, the level of achievement for girls in exact science is still weak as well as that of students in public schools. Their levels must be improved. To conduct this study, we randomly selected 300 students out of the total population of 1866 students .In addition 400 parents were questioned about the schools, 200 of each type. We chose the Student t-test to test the hypothesis of equality between the two types of comparisons (girls and boys, public and private schools). Indeed, the results of this study show a sign of weakness in the education of girls compared with boys and dominance of private schools over public schools. According Cronbach’s alpha surveys of parental satisfaction is 0.962 and 0.899, respectively (private and public). The equipment used by the researcher for data analysis is SPSS.